Systematic Literature Review (SLR): Efektivitas Informasi terhadap Ekspektasi Masyarakat pada Kebijakan Pemerintah dalam Perspektif Psikologi Komunikasi - Syafrizaldi Syafrizaldi; Agung Suharyanto; Yurial Arief Lubis (Universitas Medan Area, 2026)
This study aims to systematically examine the development and scientific findings related to the effectiveness of information in shaping public expectations of government policies using the Systematic Literature Review (SLR) method. Public policy information is understood not only as a process of conveying a message, but as a psychological stimulus that influences public perception, attitudes, and expectations. The SLR process is carried out through the stages of identification, screening, eligibility, and inclusion of literature based on the PRISMA guidelines. Literature searches were conducted on Google Scholar databases, Scopus (secondary references), and accredited national journals, with a publication range of 2000–2024. The results of the study show that the effectiveness of information is influenced by five main themes, namely the credibility of the source, the message framing strategy, the role of the media agenda, the cognitive bias of the audience, and the level of media literacy. This study confirms that public expectations of government policies are formed through complex psychological processes and mediated by public communication systems. These findings make a theoretical and practical contribution to the development of communication strategies for communication psychology and support transparent and sustainable governance.